Impact Online Learning on Students' Learning Ability in the Time of Covid 19 in Kelurahan Pabatu Kecamatan Padang Hulu Kota Tebing Tinggi - Ilham Mirzaya Putra; Annisa Rambe; Auliya Ahmad Suhardi; Rizki Wahyudi; Amalia Anjani Purba (Edumaspul: Jurnal Pendidikan, 2022)
The coronavirus forces us to keep our distance and stay away from crowds which has an impact on children's learning methods. Furthermore, the government gives an appeal to do promotions at home or on the web. Web-based learning will find that is completed online by utilizing a web network where web-based learning affects student profits in learning. Students' interest in learning at the beginning of covid in 2019 - 2020 children did not have interest in learning, but once face-to-face 50% of students' interest in learning slowly increased and after 100% face-to-face it was much different from the time of covid compared to the period before covid which greatly decreased. This study aims to determine the effect of web-based learning on learning abilities during the COVID-19 pandemic in adolescents in Kelurahan Pabatu, Kecamatan Padang Hulu, Kota Tebing Tinggi. This exploration uses subjective examination with an interview, perception, and documentation techniques. The results of the study show that the impact of learning on students during online learning is the decline in children's learning abilities and some even cannot read and count in grade 3.